Analisis Penerapan Gamifikasi Pada Pembelajaran Huruf Dan Angka Untuk Anak Usia Dini Berbasis Android - Ilyas Fauzan; Jibril Nadir (Politeknik Kampar, 2023)
The rapid development of technology today has affected all aspects of human life. During the current industrial revolution 4.0, technology plays an important role in improving the performance and connectivity of many people working in all fields including education (Damayanti et al., 2020). The use of Android by teachers and students in education during the current Covid-19 pandemic has helped a lot in delivering material, information and communication. Apart from being able to use Android to help with work, communicate with other users, use social media and play online games, it can also be used as a learning medium (Wisnumurti, 2020). One interesting method that can be implemented using Android is gamification.